Study of outcome of obstetric emergencies admitted to intensive care unit - Bahadur, B. Rao; Kodey, Prabhadevi; Tanniru, Jeevitha; Tirumala, Suhasini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Critically ill obstetric patients pose challenges to the intensive care unit team due to their altered physiology as well as due the presence of the foetus and safety of both the mother and the foetus is of paramount importance. Methods: All antenatal and postnatal cases within 42days of delivery requiring ICU admission from October 2014 to September 2016. Detailed history taken and outcome noted. Results were subjected to statistical evaluation using SSP software. Results: (n=75): obstetric reasons (n=51, 68%) of which 21(28%) had PPH and 17(22.6) had hypertensive disorders of pregnancy. Non-obstetric reasons (n=24, 32%) of which 7(9.3%) cases had jaundice and 4(5.3%) had malaria. Mechanical ventilation was needed in the majority of cases (n=44, 58.7%) followed by inotropic support (n=30, 40%).Maternal mortality was 16%. Mortality was higher (n=8, 66.6%) among patients admitted for obstetric reasons as opposed to non-obstetric indications (n=4, 33.3%). Conclusions: Early detection and prompt referral to the tertiary centre with intensive care facilities should be promoted among the medical fraternity to reduce the incidence of ICU admissions and maternal mortality. All residents of obstetrics and gynaecology should have short mandatory training phase in critical care. Multicentre randomised studies are required for formulating evidence-based national guidelines.